Day 1 Tue, March 17, 2015 2015
DOI: 10.2118/173059-ms
|View full text |Cite
|
Sign up to set email alerts
|

Defining Fragile - The Challenge of Engineering Drilling Fluids for Narrow ECD Windows

Abstract: Over the last decade, the challenge of drilling narrow Equivalent Circulating Density (ECD) window wells has put increasing pressure on the performance of the drilling fluid. As a result of this, so-called ‘Fragile Gel’, or ‘Flat Rheology’ fluids have been developed by the industry and have become widely utilised across the globe. Although the design of these fluids is primarily aimed at optimising performance in deepwater environments, the lower pressure fluctuations imposed on the formation (as compared to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…This means the drilling fluid does exhibit flat-rheology characteristics. The rheology parameters of the OBM also satisfy the rheological requirements of flat-rheology drilling fluid in Literature [6]. In addition, the OBM showcases excellent filtration property as its filtrate volume is only 3.4-5.6 mL under hightemperature (150 C) and high-pressure (3.5 MPa).…”
Section: Evaluation Of Rheological and Filtration Propertiesmentioning
confidence: 63%
See 1 more Smart Citation
“…This means the drilling fluid does exhibit flat-rheology characteristics. The rheology parameters of the OBM also satisfy the rheological requirements of flat-rheology drilling fluid in Literature [6]. In addition, the OBM showcases excellent filtration property as its filtrate volume is only 3.4-5.6 mL under hightemperature (150 C) and high-pressure (3.5 MPa).…”
Section: Evaluation Of Rheological and Filtration Propertiesmentioning
confidence: 63%
“…For the application of oil-or synthetic-based drilling fluid in deepwater drilling, the concept of "flat rheology" has been proposed. With the aim of effectively controlling the ECD and reducing the loss of drilling fluid, the concept is about maintaining a relatively stable yield point, and 10-min gel and θ6 reading of the drilling fluid in the temperature range 4.4-65 ℃ [4][5][6]. Previous studies have shown that the base oils commonly used in oil-based drilling fluid (OBM), such as mineral oils, diesels, and vegetable oils, are significantly affected by temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The results are shown in Table 4. The yield point, 10-min gel, and Ø6 value of the developed drilling fluid was stable in the wellbore temperature range 4-65°C, and it had the "flat-rheology" characteristics [8]. In addition, the drilling fluid had an excellent effect of filtration reduction, and the filtration loss was 3.2 and 3.8 mL at 100°C and 120°C respectively, and the emulsion breaking voltage was higher than 500 V. Therefore, this drilling fluid has flat rheology and good stability at 4-65°C after high temperature aging, and it can be used in field application when the downhole temperature is high.…”
Section: Evaluation Of Rheological Properties and Filtrationmentioning
confidence: 96%
“…It means that a relatively stable yield point as well as 10-min gel and 6 r/min reading (Ø6) of the drilling fluid in the deepwater wellbore are maintained in the temperature range 4.4-65°C. Therefore, the ECD of drilling fluid can be effectively controlled, and the loss of drilling fluid can be reduced [6][7][8]. Some drilling services improved the key additives of rheology modifiers and emulsifiers by developing synthetic oils; the initially developed flat-rheology synthetic-based drilling fluid solved the problem [9][10] of controlling the rheological property of the oil/synthetic-based drilling fluid in deepwater drilling.…”
Section: Introductionmentioning
confidence: 99%
“…Shale in deepwater is water sensitive, so it is prone to hydration on exposure to filtrates of water-based drilling fluid (WBDF), thus causing wellbore instability [2][3][4][5]. Serious thickening of the drilling fluid occurs in deepwater drilling when it is cooled down by the low-temperature environment (approximately 4 • C) [6][7][8], leading to operation troubles.…”
Section: Introductionmentioning
confidence: 99%